A terminal-oriented communication system - Heckel, Paul; Lampson, Butler (Communications of the ACM, 1977)
This paper describes a system for full-duplex communication between a time-shared computer and its terminals. The system consists of a communications computer directly connected to the time-shared system, a number of small remote computers to which the terminals are attached, and connecting medium speed telephone lines. It can service a large number of terminals of various types. The overall system design is presented along with the algorithms used to solve three specific problems: local echoing, error detection and correction on the telephone lines, and multiplexing of character output.